Pengaruh Serikat Pekerja dan Hubungan Industrial Terhadap Kesejahteraan Karyawan di PT. Perkebunan Nusantara III Kebun Rambutan - Jayanti, Suci Etri; Damanik, Sri Winda Hardiyanti; Damanik, Ayu Zurlaini; Saragih, Sri Wulan Dari (Economic Development Progress, 2024)
This research aims to determine the influence of labor unions and industrial relations on employee welfare at PT. Perkebunan Nusantara III Rambutan Garden. The research method used is a quantitative method using SPSS version 25.00 which was collected from the results of distributing questionnaires to employees at PT. Perkebunan Nusantara III Kebun Rambutan afdeling I and II as many as 66 people. The analytical method used in this research is using instrument tests, namely validity and reliability tests. Classic assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis tests, namely T test and F test. The results of SPSS in this research are that trade union variables influence employee welfare, relationships Industry influences employee welfare, trade unions and industrial relations simultaneously influence employee welfare.